ELECTROCHEMICAL STUDIES OF THE CONFORMATIONAL AND SODIUM-CATION COMPLEXATION PROPERTIES OF CALIX[4]ARENEDIQUINONES - Chen, Z; Gale, P; Heath, J; Beer, P (1994)
Voltammetric studies of three calix[4]arenediquinones, dimethylethercalix[4]arenediquinone (L1), diestercalix[4]arenediquinone (L2) and diamidecalix[4]arenediquinone (L3), have revealed large contributions from conformational changes of these molecules to their respective electrochemical behaviour. The reduction potential of each respective quinone moiety depends on the properties of the aromatic groups, particularly their mobility. It is proposed that the rotation of the quinone groups through the calix[4]arenediquinone cavity, while fast in the neutral state at room temperature, is slowed upon reduction. Distinguishing between simple ion pairing and true ion complexation is electrochemically demonstrated for L2 and L3 and sodium cations. The association constant for L3 and sodium cations has been electrochemically determined and is 2.0 × 105 which is in good agreement with the value obtained from UV-VIS measurements.